INSTALLATION OF SINGLE-STORY INDUSTRIAL BUILDINGS WITH REINFORCED CONCRETE FRAMES - Nomanov Mashrabjan; Adurasulova Shahnoza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the main stages and methods of installing single-story industrial buildings with reinforced concrete frames. The technologies and equipment used at various stages of construction, including foundation preparation, installation of frame elements, and roof installation, are analyzed. Special attention is paid to the safety, efficiency, and quality of installation work. The article also discusses examples of modern solutions and innovative approaches that contribute to improving the construction process.